Synthesis and structure of a family of rhodium polystannide clusters [Rh@Sn10]3–, [Rh@Sn12]3–, [Rh2@Sn17]6– and the first triply-fused stannide, [Rh3@Sn24]5–. Issue 16 (15th March 2019) - Liu, Chao; Jin, Xiao; Li, Lei-Jiao; Xu, Jun; McGrady, John E.; Sun, Zhong-Ming
Abstract : Triply fused cluster: edge shared of three [Rh@Sn10 ] subunits lead to the largest endohedral polystannide with an entirely new triply fused topology. Abstract : Through relatively subtle changes in reaction conditions, we have been able to isolate four distinct Rh/Sn cluster compounds, [Rh@Sn10 ] 3−, [Rh@Sn12 ] 3−, [Rh2 @Sn17 ] 6− and [Rh3 @Sn24 ] 5–, from the reaction of K4 Sn9 with [(COE)2 Rh(μ-Cl)]2 (COE = cyclooctene). The last of these has a hitherto unknown molecular topology, an edge-fused polyhedron containing three Rh@Sn10 subunits, and represents the largest endohedral Group 14 Zintl cluster yet to have been isolated from solution. DFT has been used to place these new species in the context of known cluster chemistry. ESI-MS experiments on the reaction mixtures reveal the ubiquitous presence of RhSn8 fragments that may play a role in cluster growth.